Efficacy and Safety of TCMI in Patients With Combined Coronary Heart Disease and Heart Failure: A Systematic Review and Network Meta-Analysis - Wei, Penglu; Yang, Kuo; Long, Dehuai; Tan, Yupei; Xing, Wenlong; Li, Xiang; Wu, Hongli; Liu, Hongxu (Frontiers in Pharmacology, 2021)
Abstract Objective To compare the efficacy and safety of TCMIs (traditional Chinese medicine injections) in treatments for patients with coronary heart disease complicated with heart failure. Methods Eight electronic literature databases (PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science, China National Knowledge Infrastructure Database, Chinese Scientific Journal database, Wanfang database, Chinese Biomedical database) were searched from their inceptions to May 18, 2021 to identify RCTs of TCMIs-CT (traditional Chinese medicine injections and conventional treatment) in the treatment of CHD-HF (coronary heart disease complicated with heart failure). The primary outcomes included the total effective rate and adverse events (ADRs). The secondary outcomes included the left ventricular ejection fraction (LVEF), N-terminal pro-brain natriuretic peptide (NT-proBNP), brain natriuretic peptide (BNP) and 6-minute walk test (6MWT). Cochrane risk-of-bias tool was used to assessed the quality of included RCTs (randomised controlled trials). Stata and OpenBUGS software were used to proceed the systematic review and network meta-analysis. Results Sixty-one eligible trials involved 5567 patients and 15 treatments: Shuxuetong injection, Shenmai injection, Shenfu injection, Shengmai injection, Danshenduofenyansuan injection, Danhong injection, Dazhuhongjingtian injection, Xinmailong injection, Dengzhanxixin injection, Gualoupi injection, Shuxuening injection, Xuesaitong injection, Yiqi Fumai injection, Shenqi Fuzheng injection. Network meta-analysis showed that Shuxuetong injection-CT group was superior to CT only in improving the total effective rate (odd ratio 7.8, 95% credible interval 1.17 to 27.41); and Shenmai injection (8.97, 4.67 to 13.18) in LVEF, Xinmailong injection (-317.70, -331.10 to -303.10) to NT-proBNP, Shenqi Fuzheng injection to BNP (-257.30, -308.40 to 242.80); Danhong injection to 6MWT (84.40, 62.62 to 106.20). Different toxicity spectrums were revealed for individual TCMIs. Conclusion TCMI combined with CT are better CT alone in treating CHD-HF. The effect of TCMIs distinct directing to different outcomes. The comparison of various TCMIs should be verified in further based on more well-designed RCTs due to the poor quality of included studies.